Striga: small seeds, big losses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Striga, a parasitic weed of most savannah crops, is gaining ground in Africa and farmers have only limited weapons against it. Its control should therefore be added to the list of priorities for research Over the last 15 years, striga has become a...